Model for End-Stage Liver Disease Score Predicts the Mortality of Patients with Coronary Heart Disease Who Underwent Percutaneous Coronary Intervention - You Chen; Min Han; Ying-Ying Zheng; Feng Zhu; Aikebai Aisan; Tunike Maheshati; Yi-Tong Ma; Xiang Xie (Cardiology Research and Practice)
Background. Coronary heart disease (CHD) is caused by the blockage or spasm of coronary arteries. Evidence shows that liver disease is related to CHD. However, the correlation between the Model for End-Stage Liver Disease (MELD) score and outcomes in patients after percutaneous coronary intervention (PCI) was unclear. Method. A retrospective cohort study involved 5373 patients with coronary heart disease after PCI was conducted from January 2008 to December 2016. Participants were classified to four groups according to the MELD score by quartiles. The primary endpoint was long-term mortality including all-case mortality (ACM) and cardiac mortality (CM). Secondary endpoints included bleeding events, readmission, major adverse cardiovascular events (MACE), major adverse cardiovascular, and cerebrovascular events (MACCE). The longest follow-up time was almost 10 years. Results. There were significant differences in the incidences of ACM (p=0.038) and CM (p=0.027) among the four MELD groups, but there was no significant difference in MACEs (p=0.496), MACCEs (p=0.234), readmission (p=0.684), and bleeding events (p=0.232). After adjusting the age, gender, smoking, drinking status, and diabetes by a multivariable Cox regression analysis, MELD remains independently associated with ACM (HR:1.57, 95%CI 1.052–2.354, p=0.027) and CM (HR:1.434, 95% CI 1.003–2.050, p=0.048). Conclusion. This study indicated that the MELD score had a strong prediction for long-term mortality in CHD patients who underwent PCI.